Morphogenesis and reproductive biology of sacred lotus (Nelumbo nucifera gaertn.) - Minimol J S (Department of Plant Breeding and Genetics, College of Horticulture, 2004)
Sacred lotus (Nelumbo nucifera) belonging to Nelumbonaceae is the only genera in that family. This legendary flower has very long and close association with history, culture, religion, literature and arts. Hence it is chosen as our national flower. Despite its immense potentialities as medicinal, ornamental and vegetable crop, this plant has received only very little attention of crop improvement workers. It was in this background the present investigation entitled ‘Morphogenesis and Reproductive Biology of Sacred Lotus’ was under taken with the objectives of evaluating the growth and development pattern of leaf, flower and seed and elucidating the reproductive biology. Six different genotypes collected from diverse ecological conditions were evaluated under ex situ conditions during December 1999 to March 2003 at College of Horticulture, Vellanikkara. Variability was observed in different biometric characters like size of lamina, longevity of leaves, petiole length etc. among the ecotypes evaluated. Study of the seasonal effect on these characters revealed that rainy season favoured growth in size of leaves and spring season favoured longevity. The growing tip of the rhizome was found to be the best propagule with respect to rhizome yield. Significant variability was observed in various floral characters among the ecotypes. Flower production started with the onset of Monsoon and reached the peak in Spring season and then declined with no flower production at all in Summer season. Flowers were found to be solitary, ebracteate, actinomorphic and complete with the different whorls arranged in a spiral fashion on the floral axis. Stigma became receptive 32 hours before flower opening and the receptivity was retained for 52 hours even after flower opening. Pollen dehiscence occurred only after complete opening of the flower bud. Pollen grains of lotus were found to be fertile, round and triporate. However, no seed set was obtained in protected buds indicating cross pollination. The temperature inside the flower bud remained between 30 to 35oC till the fourth day during the period of anthesis despite the changes in environmental temperature between 27 to 33oC. The period of this thermoregulation corresponded to receptivity of stigma. This is considered as a floral adaptation favouring cross pollination (Seymour and Schultze-Motel, 1998). Unlike other dicot, in sacred lotus, plumule emerged first and radicle was aborted. Adventitious roots were found anchoring the plant in mud. The seeds matured in 30 days after fertlization. Lotus seeds are reported to have the longest period of dormancy. The germination trials conducted after giving different pretreatments revealed that embryo as such is nondormant. Mechanical scarification followed by leaching improved germinability indicating that hard fruit wall along with thick waxy coating and water soluble inhibitors are responsible for dormancy.